Common euro bonds: Necessary, wise or to be avoided? - Paul De Grauwe; Wim Moesen; Wim Kösters; Thomas Mayer (Intereconomics, 2009)
The sharp widening of yield spreads among EMU sovereign bonds in the course of the economic crisis and concerns that some EMU member countries would encounter difficulties in rolling their existing debt and funding new budget deficits have revived proposals for a common bond issuance by EMU countries. Could these be put into practice without creating a moral hazard issue and conflicts with the no-bail-out clause of the Maastricht Treaty? Would the establishment of a European Monetary Fund offer better prospects of overcoming the present problems?
Keywords: 330